Does history deal with fact or is it a narrative art? - Landripet, Ivan (2002)
Before the age of modernity, there had been counts of various material and non-material objects of culture that had prevented history from being forgotten. Those can provide us with a narrative of the past, but it was actually the epoch of modernity that established a cult of constituting and accumulating history, an obsessive idea of history being based on one central reason, thelos, which leads to the present. According to some historians, it were the Christians that imperatively had to see history as being universal, because of the theological reasons. But modernity was what really turned history into an instrument serving the rulers of the newly emerging nation-states. At that exact point, a universal, global, normative, and all-institutions-of-society-invading concept of human history is being established, with multitude of national histories embedded in it. It’s a machine producing historical truth: a particular historical narrative is imposed as an ontological truth. And this body of knowledge necessarily gets updated from time to time, as we all had an opportunity to see in relation to political, social and economic changes that took place in our own societies recently. There is, to give only one example, a direction within historical thought, closely related to sociology, which is shifting history toward social history. It’s the Anally school of France, promoting new tendencies in the interpretation of historical facts and documents. The school aims to reveal a stable underlying structure behind the simple historical narrative, to offer a new interpretation of history. To put it in the words of jilted generations, it’s a shift from winners’ history to the history of loosers, those that were marginal in terms of power, excluded from the positions in official historical discourses and from the collective memory.
ENG